Régimen jurídico de las aguas subterráneas en el Perú - Cairampoma Arroyo, Alberto; Villegas Vega, Paul (Pontificia Universidad Católica del Perú, 2016)
This article studies the legal regime of groundwater by analyzing the context of integrated water resources management and recognizing its definition and characteristics.Furthermore, it analyses the ownership of ground water, the planning regime applicable, the exploration and exploitation activities, their authorization certificates, the activity of supervision over them, and finally the article describes the special schemes for management and limitation recognized in Peruvian law.

En el presente artículo se estudia el régimen jurídico de las aguas subterráneas, analizando el marco de la gestión integrada de recursos hídricos y reconociendo su definición y particularidades.Asimismo, se analiza la titularidad de las aguas subterráneas, el régimen de planificación aplicable, las actividades de exploración y explotación, sus títulos habilitantes, la actividad de supervisión que sobre ellas recae, para finalmente, dejar anotados los regímenes especiales de gestión y limitación reconocidos en el ordenamiento jurídico peruano.
Legal regime ground water in Peru
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01